Electromagnetic absorbing materials - Mušič, Branka (Informacije MIDEM, 2011)
Around 15 years have passed since the wireless technologies started with rapid development. During that time, different fields of electromagnetic waves have become more active. As a result of rapid advances in technology the use of wireless communication and radar systems is expanding quickly, which leads to a significant increase in the levels of background electromagnetic (EM) radiation. To avoid potential health effects from high exposure to electromagnetic waves, unnecessary EM waves should be eliminated to protect human bodies, especially expectant mothers and children. In European Pre-standard ENV 50166-2:1995 - Human exposure to electromagnetic fields - High frequency, is stated that electromagnetic fields interact with the human body and other systems through a number of physical mechanisms. Therefore, it is necessary to protect all of these systems. As mentioned in ENV standard, it is recognized that additional considerations have been made by some countries, regarding the reference levels as minimum requirements in certain frequency ranges. Those considerations resulted in additional reference marging. This is the reason why is nowhere a background of electromagneticwaves including many reviews of diverse articles on topics of electromagnetic materials. We decided to bring out that summery to deliver this diversified information to all types of readers, both technical and non-technical.
Keywords: electromagnetic waves; elektromagnetno valovanje; feromagnetni materiali; ferromagnetic materials; magnetic composite; magnetni kompoziti; measurements; meritve; microwaves; mikrovalovi